2003
DOI: 10.1017/s0009443903000196
|View full text |Cite
|
Sign up to set email alerts
|

Religion in China Today: Introduction

Abstract: In the last 20 years religious traditions in many parts of China have revived their activities and organizations and rebuilt their temples, mosques and churches, despite decades of strict regulation and repression by the government. This revival is an aspect of the greater social freedom that has accompanied the economic development and diversification of that period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…From the legal perspective, the Constitution of China in 1982 provides that citizens have freedom of religion. Religious festivals are held, traditional funerals and burial rituals are restored, destroyed images and shrines are rebuilt, priests reappear to organize rituals, and congregations meet to worship (Overmyer 2003). In recent years, the government's attitude toward religious activities has become unprecedentedly friendly, as the party leaders realize that religion helps fill a vacuum created by the country's breakneck growth and rush to get rich ).…”
Section: Introductionmentioning
confidence: 99%
“…From the legal perspective, the Constitution of China in 1982 provides that citizens have freedom of religion. Religious festivals are held, traditional funerals and burial rituals are restored, destroyed images and shrines are rebuilt, priests reappear to organize rituals, and congregations meet to worship (Overmyer 2003). In recent years, the government's attitude toward religious activities has become unprecedentedly friendly, as the party leaders realize that religion helps fill a vacuum created by the country's breakneck growth and rush to get rich ).…”
Section: Introductionmentioning
confidence: 99%
“…Various religious associations have been restored on the national and local level (Ashiwa and Wank 2006). Numerous temples, churches and mosques have been built or redecorated in towns and villages (Overmyer 2003;Dean 2003;Madsen 2003;Hillman 2004). The next-generation religious leaders are trained in Buddhist academies, Daoist schools, Christian seminaries, and Islamic institutes (Birnbaum 2003, p. 440;Dean 2009, pp.…”
Section: Religious Restrictions In Contemporary China and Their Rootsmentioning
confidence: 99%
“…Buddhism has been a major religion in China, and many studies have shown its revival in the reform era (e.g., Overmyer, 2003). One major difference of Buddhism from Christianity is its syncretistic characteristics.…”
Section: Buddhism: a Preliminary Comparisonmentioning
confidence: 99%